2013
DOI: 10.1038/srep02364
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of Alzheimer's disease brains

Abstract: Alzheimer's disease (AD) is an irreversible, progressive brain disease and can be definitively diagnosed after death through an examination of senile plaques and neurofibrillary tangles in several brain regions. It is to be expected that changes in the concentration and/or localization of low-molecular-weight molecules are linked to the pathological changes that occur in AD, and determining their identity would provide valuable information regarding AD processes. Here, we propose definitive brain metabolic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 64 publications
9
118
0
Order By: Relevance
“…Increased levels of three polyamines, putrescine, spermidine and spermine, have been reported in brain tissue and plasma from AD patients (Inoue et al, 2013;Trushina et al, 2013). The underlying explanation for this is that Aβ causes up-regulation of polyamine uptake and increased ornithine decarboxylase activity, which leads to increased polyamine synthesis (Yatin et al, 1999;Yatin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of three polyamines, putrescine, spermidine and spermine, have been reported in brain tissue and plasma from AD patients (Inoue et al, 2013;Trushina et al, 2013). The underlying explanation for this is that Aβ causes up-regulation of polyamine uptake and increased ornithine decarboxylase activity, which leads to increased polyamine synthesis (Yatin et al, 1999;Yatin et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In fact it can be especially useful to get the benefit from the potential to discover novel unforeseen metabolic factors or biomarkers in fingerprinting approaches with the option of demonstrating the observed changes of known metabolites or confirming the potential biomarkers by means of the metabolic profiling mode [96]. A recent study followed this comprehensive metabolomics approach in the investigation of biomarkers for AD by the comparison of postmortem brain tissue from AD patients and healthy control subjects [97]. First, a metabolic fingerprint to determine potential biomarkers and affected pathways in AD pathology was performed.…”
Section: Metabolomics In Admentioning
confidence: 99%
“…First, a metabolic fingerprint to determine potential biomarkers and affected pathways in AD pathology was performed. Then the specific metabolic pathway related to potential AD biomarkers spermine and spermidine, namely biogenic polyamine metabolism, was explored in detail finding three more molecules altered due to AD pathology [97].…”
Section: Metabolomics In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been performed in biofluids because of the difficult availability of human brain tissue. Thus, only a few preliminary studies have been previously reported in this subject [12][13][14], demonstrating the potential of this approach.…”
Section: Introductionmentioning
confidence: 99%